Studies on Cyanex-272 Complexes of Mg (II), Ca (II) and Fe (III) - Islam, M Badrul; Haque, M Zahurul; Islam, N Shamsul (Bangladesh Journal of Scientific and Industrial Research, 2008)
Certain complex compounds were synthesized by the interaction of Mg(II), Ca(II) and Fe(III) halides with the solvent extracting reagent, Cyanex-272 i.e. bis (2,4,4- trimethylpentyl) phosphinic acid as ligand. All the prepared complexes have been characterized on the basis of their molar masses, conductivity, magnetic measurements and infrared and electronic spectral studies. The other physico-chemical properties e.g. colour, decomposition temperature have also been ascertained. Key words: Chanex-272Bangladesh J. Sci. Ind. Res. 42(4), 475-482, 2007